A modulated model predictive control scheme for the brushless doubly-fed induction machine - Li, Xuan; Peng, Tao; Dan, Hanbing; Zhang, Guanguan; Tang, Weiyi; Wheeler, Patrick (2017)
This paper proposes a modulated model predictive control (MMPC) algorithm for a brushless double-fed induction machine. The Brushless Doubly-Fed Induction Machine has some important advantages over alternative solutions for brushless machine applications. The proposed modulation technique achieves a fixed switching frequency, which gives good system performance. The paper examines the design and implementation of the modulation technique and simulation results verify the operation of the proposed modulation technique.